Magic in Greco-Roman Era: A Historical Context to Understand Magic in the Acts of the Apostles - Chandra Han (Sekolah Tinggi Theologia Jaffray, 2020)
Magic is an important topic in the New Testament but compared to other topics of discussion in New Testament Studies, the significance of the theme of magic has been unjustly undermined as indicated by David E. Aune. From the all eight occurrences of magic in the New Testament, four are found in the Acts of the Apostles. Therefore, the Acts of the Apostles is the most significant source to understand magic in the New Testament. The purpose of this thesis is to demonstrate the significant of magic in the Greco-Roman era as the historical context to understand magic in the Acts of the Apostles. Since Christianity flourished in the Greco-Roman era, the understanding of magic in the Greco-Roman era is significant to understand its confrontation with Christianity in the Acts of the Apostles. This article will analyze mainly the first source of magic in the Greek magical papyri, the definition of magic, its principles, and its spell related to the Acts of the Apostles, and the relation between magic and religion in Greco-Roman Era. The judgment on magic will then be provided in the end of this article as the foundation to further study of the Acts of the Apostles.